Aggregate Interference Power Characterization for Directional Beamforming Wireless Networks - Abusabah, Ayman T. (2021)
partially supported by the projects CoSHARE (LISBOA-01-0145-FEDER0307095 - PTDC/EEI-TEL/30709/2017), and UIDB/50008/2020.